PEMAHAMAN PARENTING ORANG TUA TERHADAP KESELAMATAN LALU LINTAS UNTUK ANAK USIA DINI DI TK KARYA BUNDA - Alfian Saleh; Muthia Anggraini; Sean Marta Efastri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Discipline attitude cannot be formed quickly including in forming traffic discipline. Cooperative learning methods regarding traffic for early childhood is one way to prevent traffic accidents that can be instilled early. Traffic safety education activities for the Karya Bunda Kindergarten in Sei Kijang Subdistrict, Pelalawan District are very necessary because the Karya Bunda Kindergarten is located on the east side roadside which is an accident-prone area with very minimal signs and the absence of the Zona Selamat Sekolah (ZoSS) area. This community service activity uses the method of implementing traffic safety by involving parents as role models for their children. The stages of this activity process are given by the parents the Preetest to measure the parents' initial ability in understanding safety riding, then material and case studies are carried out in planting traffic moral values, especially when carrying children in driving. after being given the material and finally involving the students in coloring the sign image about a case study in driving a vehicle accompanied by parents of students.The results of this activity increased the level of understanding of parents by an average of 25.12% from the results of the Preetest and Postes. It is hoped that the increase and implementation of orderly traffic can foster awareness of students and parents of TK Karya Bunda's parents to behave safely increase with parents as pioneers.